Analisis Minat Belajar Matematika Siswa Kelas IV Sekolah Dasar Neger 007 Pulau Birandang - Miftahul Jannah (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This research aim to analyze the learning interest of class IV student at SDN 007 Pulau Birandang towards mathematics learning. The research method used is descriptive research method used is descriptive research using a Likert scale. The population in this research is class IV students at SDN 007 Pulau Birandang and the sample taken is class IVA, numbering 20 the instrument used was a statement questionnaire with indicators of student interest in learning consisting of 30 statements. Based on the results of data analysis, the highest percentage was found in the indicator of feelings of happiness with a total 62.5%.this shows that the majority of students enjoy mathematics lessons